Isolation of Phenolic Compounds from Acacia nilotica with Topical Antiinflammatory Activity - Chaubal, Rohini; Mujumdar, A.M.; Misar, Ashwini; Deshpande, N.R. (Asian Journal of Chemistry, 2016)
A quath of Acacia nilotica was prepared according to Ayurvedic method from powder of shae dried aerial parts of the plant. Chromatographic separation by repeated column chromatography followed by purification using mixed solvent crystallization of the quath yielded the phenolic compounds 3,5-dihydroxy-4-methoxy benzoic acid (1) and 3,4-dimethoxy-4-hydroxy benzoic acid (syringic acid, 2). Both these compounds are known compounds and have been isolated for the first time from this plant. Antiinflammatory activity was also studied for compound 1.